1970
DOI: 10.3329/bmrcb.v36i3.7286
|View full text |Cite
|
Sign up to set email alerts
|

Feeding practice in acute stroke patients in a tertiary care hospital

Abstract: Background: Feeding is a basic component of care and it is the most common and difficult management issue for stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…Patients who are capable of swallowing liquids and food may have a poor appetite because of the effects of inter current illness or medication and they may eat more slowly or be less keen to eat because of facial weakness, lack of dentures or poor arm function 18 . In a Bangladeshi study it has been reported that this cause to be 22.0% which is comparable to this present study 17 . Out the 100 patients studied, 71 patients had complications.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Patients who are capable of swallowing liquids and food may have a poor appetite because of the effects of inter current illness or medication and they may eat more slowly or be less keen to eat because of facial weakness, lack of dentures or poor arm function 18 . In a Bangladeshi study it has been reported that this cause to be 22.0% which is comparable to this present study 17 . Out the 100 patients studied, 71 patients had complications.…”
Section: Discussionsupporting
confidence: 91%
“…Two previous Bangladeshi studies conducted by Siddique et al and Hossain also describes similar findings 14,16 . In a study done by Miah et al, reported that 78% of the stroke patients' required NG tube feeding for stroke 17 . Indications for NG tube feeding were analyzed in our study population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations